Forming layered conjugated porous BBL structures. Issue 30 (3rd July 2019) - Shin, Sun-Hee; Noh, Hyuk-Jun; Kim, Young-Hyun; Im, Yoon-Kwang; Mahmood, Javeed; Baek, Jong-Beom
Abstract : Ladder-like poly(benzoimidazobenzophenanthrolines) (BBLs) have attracted great interest due to their outstanding features, including thermal and chemical stability, electrical conductivity, and optical and electronic properties. Abstract : One-dimensional (1D) ladder-like poly(benzoimidazobenzophenanthrolines) (BBLs) have attracted great interest due to their outstanding features, including thermal and chemical stability, electrical conductivity, and optical and electronic properties. Nevertheless, layered conjugated porous BBL structures have not yet been reported to date. Here, we introduce two-dimensional (2D) layered BBL structures via the polycondensation of mellitic anhydride (MTA) as an A3 monomer with 1, 2, 4, 5-tetraaminobenzene (TAB) as the B2 monomer, or hexaaminobenzene (HAB) as the B3 monomer in polyphosphoric acid (PPA). The porous 2D BBL network structures are constructed of robust fused aromatic rings and thus exhibit high thermal stability and high Brunauer–Emmett–Teller (BET) surface areas with different pore diameters and permanent microporosities. The 2D BBL networks demonstrated high gas uptake capacities for hydrogen (H2, 1.65 wt% at 77 K, 1 bar) and carbon dioxide (CO2, 15.6 wt% at 273 K, 1 bar) with unusually high Q st values.